Lazer e consumo na percepção dos estudantes universitários - Márcia Botelho Oliveira; Neuza Maria da Silva; Renato Mareto (Ciências Sociais Unisinos)
The relation between leisure and consumption is visible in Western society and has been strengthened by the media, which in the last decades has been suggesting the forms of leisure to be enjoyed by people. Thus the objective of this study was to identify and analyze leisure activities of undergraduate and graduate students of a Federal University in order to find out whether such activities are related to the act of consuming. Three hundred students participated in the survey: 246 undergraduates and 54 graduates. Data were quantitatively analyzed using the Statistical Package for Social Sciences – SPSS, version 17.0, with which we performed exploratory and variance analysis, Cronbach’s Alpha cal- culation, frequency analysis and cross tabulations. The most cited activities as the main form of leisure enjoyed by the students required spending money and the second most cited reason for not enjoying leisure more often was related to their financial situation. Regarding the level of satisfaction with leisure in the city of Viçosa (MG), we noticed that students who spend more time watching television were more unsatisfied than the others. If advertising is capable of influencing young people surrounded by opportunities and knowledge, as shown in this study, the influence of marketing strategies on the portion of the population which does not have the same opportunities to study is alarming. Thus we confirm the need for education for a conscious consumption which separates leisure from consumption. Such education should be part of the curriculum in elementary and high schools, as well as colleges and universities.